BODY MASS INDEX AND TOTAL SERUM LEPTIN LEVEL IN ABORTION (Iraqi Journal of Medical Sciences, 2016)
Background:Adipose tissue secretes variety of adipokines, including leptin, which is involved in endocrine processes regulating reproduction and plays an important role in energy metabolism and fetal development during pregnancy.Objectives:To investigate the relationship between total serum leptin concentrations and anthropometric parameters including body mass index (BMI) in aborted women at the second trimester.Methods: A case control study was carried out from November 2011 to April 2012. The patients' group includes 30 aborted women at the second trimester. They were collected from Al-Elweyia, Al-Hakeem and Al-Khadhemiyia Teaching Hospital in Baghdad. Thirty healthy pregnant women (at their second trimester of gestation) were used as control. Patients and control were comparable in age. Blood HbA1c and serum concentrations of total leptin, lipid profile, and glucose were measured in both groups.Results:Total serum leptin concentration were significantly lower in those with abortion at the second trimester compared with healthy pregnant control (3.5±0.8 pg/ml vs. 24.4±0.7 pg/ml, P = 0.0001) and leptin/BMI ratio vs. control (0.1±0.02 vs. 0.9±0.01 ml, P=0.0001). No correlation was found between leptin level and patient’s age or gestational age in the case group. Highly significant correlation was found between patient’s total serum leptin and their body mass index, HDL-C, total cholesterol/HDL-C ratio and atherogenic index (P < 0.0001).Conclusion:The significant correlation between patient’s leptin and their BMI in addition to Leptin/BMI ratio even in non obese patient supports our objective that the unexplained abortion at second trimester is due to abnormality in their metabolic hormone action and reflect leptin resistance condition.Keywords:Second trimester abortion, Leptin, BMI, Gestational age.